How Escherichia coli Circumvent Complement-Mediated Killing - Abreu, Afonso G.; Barbosa, Angela S. (Frontiers in Immunology, 2017)
Complement is a crucial arm of the innate immune response against invading bacterial pathogens and one of its main functions is to recognize and destroy target cells. Like other pathogens, E. coli has evolved mechanisms to overcome complement activation. It is well known that capsular polysaccharide may confer resistance to complement-mediated killing and phagocytosis, being one of the strategies adopted by this bacterium to survive in serum. In addition, proteases produced by E. coli have been shown to downregulate the complement system. Pic, an autotransporter secreted by different pathogens in the Enterobacteriaceae family, is able to cleave C2, C3/C3b, C4/C4b, and works synergistically with human Factor I (FI) and Factor H (FH), promoting inactivation of C3b. EspP, a serine protease of enterohemorrhagic E. coli, downregulates complement activation by cleaving C3/C3b and C5. StcE, a metalloprotease secreted by EHEC, inhibits the classical complement-mediated cell lysis by potentiating the action of C1-INH, and the periplasmic protease Prc contributes to E. coli complement evasion by interfering with the classical pathway activation and by preventing MAC deposition. Lastly, it has been described that E. coli proteins interact with negative complement regulators to modulate complement activation. The functional consequences resulting from the interaction of OmpA, NlpI, OmpW and Stx2 with proteins of the FH family and C4b binding protein (C4BP) are discussed in detail. In brief, in this review we focused on the different mechanisms used by pathogenic E. coli to circumvent complement attack, allowing these bacteria to promote a successful infection.